Developing a Book for Teaching Reading Skills in the Context of Local Culture: The Department of Arabic Language Teaching at Indonesia University | Tathwir Kitab li-Ta'lim Maharat al-Qira'ah fi Siyaq al-Thaqafah al-Mahalliyyah: Qism Ta'lim al-Lughah al-'Arabiyyah fi Jami'ah Indonesia - Suwandi, Suwandi; Sutaman, Sutaman; Ulum, M. Samsul; Alzitawi, Diaya Uddeen Deab Mahmoud; Supangat, Supangat (Institut Agama Islam Negeri Palangka Raya, 2024)
Students do not have a specific book for learning maharah qiro